A Qualitative Analysis of Clinical Year Veterinary Student Journal Entries for a Shelter Medicine Rotation - Jafarian, Sohaila; Akpek, Eda; Reinhard, Chelsea L.; Watson, Brittany (Frontiers in Veterinary Science, 2022)
Veterinary medical schools are tasked with not only providing experiences necessary to graduate veterinarians proficient in the skills and knowledge used most frequently in private practice, but also develop expertise in animal behavior, welfare, ethics, veterinary forensics, and cultural competency. Integrating all these knowledge areas into the curriculum can be challenging. Shelter medicine is increasingly identified by educators as an optimal learning environment to offer exposure to these topics. It can not only meet learning objectives in veterinary medical curriculum, but also provide students with authentic learning experiences to engage in and gain a deeper understanding of cultural humility, implicit bias, diversity, and inclusion. This includes documentation of international learning outcomes for shelter medicine in veterinary medical curriculum. There have been no studies evaluating authentic learning experiences specific to shelter medicine programs and their impacts on students. The aim of this study was to determine the individual activities and thematic categories on which veterinary students chose to reflect on and their potential impacts during a clinical rotation in shelter medicine at Penn Vet through qualitative content analysis of their journal entries. In our study, students found experiences on the shelter medicine rotation to be beneficial to their growth as a future veterinarian, provided them with takeaways that they found applicable and practical, helped them self-identify knowledge gaps, and changed their perspectives on several important topics related to collective human and animal welfare. These results speak to the value perceived by students of the rotation and suggest an authentic learning experience through a shelter medicine program can help cultivate more practice-ready and culturally competent veterinary graduates.